2015
DOI: 10.1299/jtst.2015jtst0007
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the distance between fuel and oxidizer nozzles on NOx emissions from spray combustion furnaces incorporating high-temperature preheated oxidizers

Abstract: The objective of the present study was to investigate the effect of the distance between fuel and oxidizer nozzles on NOx emissions from a laboratory-scale spray combustion furnace simulating an industrial high-temperature air combustion (HiTAC) furnace. The furnace employed in these trials was fueled with commercially obtainable kerosene in combination with highly preheated oxidizer gases. The oxidizer was pre-diluted by the addition of nitrogen in order to produce dilution levels equivalent to those in indus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…As extensively discussed in the literature, the geometry of the burner (with particular reference to the fuel and air jet nozzles) plays an important role since it allows to obtain large exhaust recirculation and turbulence intensity, as required to reach MILD combustion conditions.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…As extensively discussed in the literature, the geometry of the burner (with particular reference to the fuel and air jet nozzles) plays an important role since it allows to obtain large exhaust recirculation and turbulence intensity, as required to reach MILD combustion conditions.…”
Section: Methodsmentioning
confidence: 99%
“…Among the others, Weber et al 32 studied NOx emission from a semi-industrial highly preheated air furnace with light and heavy oils as fuels; they found that NOx reduction requires an optimized burner design in terms of distance between fuel and oxidizer injectors. The effects of the nozzle distance on NOx emissions were studied also by Nada et al 33 in a laboratory-scale furnace with kerosene as a liquid fuel. Derudi and Rota 34 investigated the sustainability of MILD combustion of liquid linear and branched hydrocarbons in a dual-nozzle laboratory-scale burner; they found that MILD combustion conditions seems more affected by the physical state of the fuel than by the chain length of the hydrocarbons.…”
Section: Introductionmentioning
confidence: 97%
“…There have been several studies on MILD combustion, both experimentally and numerically, such as; effects of geometry and operating condition, the effect of burner configuration (Nada et al, 2015;Lee et al, 2019a), furnace chamber configuration (Schaffel-Mancini et al, 2010;Tu et al, 2015a), jet velocity of reactant (Mi et al, 2011;Veríssimo et al, 2013), reactant temperature (Khoshhal et al, 2011;Huang et al, 2014), chemical composition of fuel and oxidizer (Dally et al, 2004;Tu et al, 2015b;Lee et al, 2019b), on NOx formation and reduction (Wünning and Wünning, 1997;Mancini et al, 2002) and microscopic characteristics (Jin and Zhou, 2015;Zhang et al, 2019;).…”
Section: Introductionmentioning
confidence: 99%